2016
DOI: 10.1002/bio.3170
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured luminescently labeled nucleic acids

Abstract: Important and emerging trends at the interface of luminescence, nucleic acids and nanotechnology are: (i) the conventional luminescence labeling of nucleic acid nanostructures (e.g. DNA tetrahedron); (ii) the labeling of bulk nucleic acids (e.g. single-stranded DNA, double-stranded DNA) with nanostructured luminescent labels (e.g. copper nanoclusters); and (iii) the labeling of nucleic acid nanostructures (e.g. origami DNA) with nanostructured luminescent labels (e.g. silver nanoclusters). This review surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 114 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Lipid, peptide and DNA are all attractive surface ligands for MOFs . Among these, due to DNA designable sequence and precise base‐pairing properties, DNA has been a superstar molecule in the field of nanomaterials …”
Section: Introductionmentioning
confidence: 99%
“…Lipid, peptide and DNA are all attractive surface ligands for MOFs . Among these, due to DNA designable sequence and precise base‐pairing properties, DNA has been a superstar molecule in the field of nanomaterials …”
Section: Introductionmentioning
confidence: 99%
“…In addition, metal NCs can be stabilized with ligands such as DNA, proteins, polymers. [ 27–31 ] The peroxidase‐like activity of bovine serum albumin (BSA)–Au NCs was first reported by Wang's group. [ 32 ] Subsequently, Chen's group found that the BSA–Au NCs could enhance the CL emission of the luminol–H 2 O 2 reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The overall number of publications involving ECL has increased year‐by‐year . A great deal of ECL luminophores and the detailed ECL mechanisms have been extensively studied by many researchers, and well summarized in several reviews . Therefore, in this review, ECL substrates and their related luminescent mechanisms are not presented in detailed.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] A great deal of ECL luminophores and the detailed ECL mechanisms have been extensively studied by many researchers, [11,15,21,[33][34][35][36][37][38] and well summarized in several reviews. [7,31,32,[39][40][41][42] Therefore, in this review, ECL substrates and their related luminescent mechanisms are not presented in detailed.…”
mentioning
confidence: 99%